ESC 2019 guidelines on chronic coronary syndromes: could calcium scoring improve detection of coronary artery disease in patients with low risk score. Findings from a retrospective cohort of patients in a district general hospital. (July 2021) - Fyyaz, S; Rasoul, H; Miles, C; Olabintan, O; David, S; Plein, S; Alfakih, K
Background: The European Society of Cardiology (ESC) published an updated stable chest pain guideline in 2019, recommending the use of an updated pre-test probability (PTP) risk score (RS) to assess the likelihood of coronary artery disease (CAD). We sought to compare the 2019 and 2013 PTPRS in a contemporary cohort of patients. Methods: 612 patients who were investigated with computed tomography coronary angiography (CTCA) for stable chest pain were included in a retrospective analysis. Results: There were 255 patients with 2019 PTPRS 15–50% with a 9% yield of severe CAD on CTCA, compared with 402 patients and a 4% yield using the 2013 PTPRS (p = 0.01). 355 patients had a 2019 PTPRS of <15%, with 3% found to have severe CAD, compared with 67 patients and none with severe CAD using the 2013 PTPRS (p = 0.14). 336 of patients with 2019 PTPRS of <15% had a calcium score as part of the CTCA. 223 of these had a zero calcium score and only one had severe CAD. In comparison, 113 patients had a positive calcium score, and 10 (9%) had severe CAD (p < 0.001). Discussion: The ESC 2019 PTPRS classifies more patients as at lower risk of CAD and hence reduces the risk overestimation associated with the 2013 PTPRS. However, in patients with a 2019 PTPRS of <15%, who would not be investigated, the use of the calcium score detected the majority of patients with significant CAD, who may benefit from secondary prevention and an associated mortality benefit as per the SCOT-Heart trial.